2011
DOI: 10.1007/s11136-010-9827-x
|View full text |Cite
|
Sign up to set email alerts
|

A Spanish version of the athens insomnia scale

Abstract: Objectives To develop and validate a Spanish version of the Athens Insomnia Scale (AIS). Methods The AIS is designed to assess sleep difficulty and comprises eight items: the first five refer to the sleep disturbance and the last three to the daytime consequences. Either the full eight-item scale (AIS-8) or the brief form (AIS-5) can be administered. The adaptation used a backtranslation design. The validation process was based on a sample of 323 participants (undergraduates, community sample and psychiatric o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
3
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 29 publications
(35 reference statements)
4
49
3
8
Order By: Relevance
“…Therefore, an examination of whether the same results would be obtained from a population sample that includes all generations is necessary. Finally, as in previous studies, 12,25 sample participants who were recruited from the community did not undergo a face-to-face assessment to clarify whether they had concomitant sleep disorders; these participants were merely those who had not received previous treatment for sleep or psychiatric disorders and produced normal PSQI-J scores. Nonetheless, this study shows that the AIS-J has high validity, and as the scale is both convenient to administer and has a high accuracy, the AIS-J can be expected to have high utility not only in epidemiological research but also for clinical evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an examination of whether the same results would be obtained from a population sample that includes all generations is necessary. Finally, as in previous studies, 12,25 sample participants who were recruited from the community did not undergo a face-to-face assessment to clarify whether they had concomitant sleep disorders; these participants were merely those who had not received previous treatment for sleep or psychiatric disorders and produced normal PSQI-J scores. Nonetheless, this study shows that the AIS-J has high validity, and as the scale is both convenient to administer and has a high accuracy, the AIS-J can be expected to have high utility not only in epidemiological research but also for clinical evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…All three scales have been shown to have appropriate diagnos-tic utility and include a set of items for evaluating both nocturnal sleep disturbance and daytime dysfunction. In regard to the specific characteristics of each scale, the item for frequency of sleep medication use is set only in the PSQI, 8 while the ISI is capable of categorizing insomnia severity as follows: absence of insomnia (0-7), sub-threshold insomnia (8)(9)(10)(11)(12)(13)(14), moderate insomnia (15)(16)(17)(18)(19)(20)(21), and severe insomnia (22)(23)(24)(25)(26)(27)(28). 11 The AIS was created to assess the severity of insomnia on the basis of the ICD-10 15 diagnostic criteria for insomnia.…”
mentioning
confidence: 99%
“…Subjects with an AIS score ≥6 were considered to be suffering from insomnia 12. The AIS is considered an excellent instrument for assessing subjective sleep quality in both clinical and study settings as it has good reliability and validity9 and is easy to complete 13…”
Section: Methodsmentioning
confidence: 99%
“…Scores that are higher than six define the presence of insomnia [17]. There are many publications with AIS, available in many languages including Spanish [23] [Appendix B]. The scale evaluates the events experienced in the last month; its brevity and simplicity allows its application in clinical or community settings.…”
Section: Resultsmentioning
confidence: 99%
“…It has been noted the high degree of internal consistency with a Cronbach's alpha of 0.90 showed by AIS in the general population [23]. It has been demonstrated that daily activities and the presence of menopausal symptoms have an important role in the establishment of insomnia states in Latin America.…”
Section: Resultsmentioning
confidence: 99%